PENGARUH STORE ATMOSPHERE, KERAGAMAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN AWANBREW COFFEE KOTA PASURUAN - Chairunnisaa, Izzah Riastiti; Mufidah , Eva; Wahyuni, Hari (Jurnal Pijar, 2024)
This research aims to determine the influence of store atmosphere, product diversity and service quality on customer satisfaction at Awanbrew Coffee, Pasuruan City. The population used is customers who have made at least 1 purchase at Awanbrew coffee within a period of 1 year with ages 19-40 years using a non-probability sampling method. The sampling technique used purposive sampling technique, so that there were 73 respondents as samples and data analysis was carried out using the SPSS program. The analysis used is Instrument Test, Coefficient of Determination Analysis and Hypothesis Test and Dominant Influence Test. The results of this research show that simultaneously store atmosphere, product diversity and service quality have a significant effect on customer satisfaction. Partially, store atmosphere does not have a significant effect on customer satisfaction, while weight diversity and service quality partially have a significant effect on customer satisfaction. The regression results obtained were R2 of 0.570 or 57.0% with an X1 value of 0.401 or 40.1%, an X2 value of 0.545 or 54.5% and an X3 value of 0.518 or 51.8%.